Laboratory performance of asphalt rubber mixtures - Fontes, Liseane P. T. L. (2009)
Asphalt rubber mixtures are one of the most promising techniques to extend the service of asphalt pavement overlays. Asphalt rubber binder is composed of crumb rubber from reclaimed tires and conventional asphalt. The asphalt rubber binder can be obtained through wet process in two different systems: tire rubber-modified asphalt binder (produced at industrial plants and continuous blending (produced in asphalt plants). This study presents a laboratory evaluation of asphalt rubber mixtures produced with different asphalt rubber binders, using gap and dense gradations. The mechanical behaviour of the mixtures studied was established through several laboratory tests (stiffness, fatigue and permanent deformation,). Moreover, the morphologies of the crumb rubber and of the asphalt rubber binder were analysed through scanning micrographs. The rheology of the asphalt rubber binder was characterised in order lo predict the mechanical behaviour of asphalt rubber mixtures.